Children of the divide - Tomlinson, Patrick S. (Tomlinson, Patrick S. Children of a dead earth, 2017)
"A new generation comes of age eighteen years after humanity arrived on the colony planet Gaia. Now threats from both within and outside their Trident threaten everything they've built. The discovery of an alien installation inside Gaia's moon, terrorist attacks and the kidnap of a man's daughter stretch the community to breaking point, but only two men stand a chance of solving all three mysteries before the makeshift planetary government shuts everything down."--